2018
DOI: 10.1371/journal.pone.0205134
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a simple pharmacovigilance program to improve reporting of adverse events associated with biologic therapy in rheumatology: Preliminary results from the Calabria Biologics Pharmacovigilance Program (CBPP)

Abstract: IntroductionPost-marketing surveillance activities (namely pharmacovigilance) are crucial to favor the early detection of unexpected adverse events (AEs) and/or serious adverse reactions (SAEs). Indeed, spontaneous reporting of AEs has been demonstrated to underestimate the number of events in different clinical settings. Aim of the present study is to report the preliminary data of a Regional (Calabria, Italy) Pharmacovigilance Program (CBPP) aimed at improving AEs’ reporting associated with biologics use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 31 publications
(31 reference statements)
2
21
0
Order By: Relevance
“…Spontaneous reporting of suspected AEs, and above all programs of active pharmacovigilance, can provide a rapid and early detection of adverse events potentially related to drugs but a high under reporting rate, with an overall estimate of only 6–10% of all AEs described, is widespread [ 9 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spontaneous reporting of suspected AEs, and above all programs of active pharmacovigilance, can provide a rapid and early detection of adverse events potentially related to drugs but a high under reporting rate, with an overall estimate of only 6–10% of all AEs described, is widespread [ 9 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Calabria Biologics Pharmacovigilance Program (CBPP) is a multicentre pharmacovigilance study as previously described [ 9 , 13 ]. Briefly, CBPP is a multicenter pharmacovigilance study aimed at improving the continuous monitoring of safety of treatment with biologic drugs in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ADRs most documented in different studies are those related to infections [14,15,[19][20][21], general manifestations or those associated with the administration of biotech drugs [12,22,23] and those related to the skin or subcutaneous tissues [4,12,23,24]. However, the present study found that the most common ADRs were those related to the respiratory tract, diverging with what was found in other studies where their frequency was much lower (16.8 vs. 3.8-10.8%) [4,12,24], probably because we included in this category infections such as pneumonia and bronchitis, among others, which increased the proportion of respiratory tract-related ADRs.…”
Section: Discussionmentioning
confidence: 99%